Transition-Metal-Free Strategies for the Synthesis of C-1 Aryl-Substituted Tetrahydroisoquinolines - Singh, Pushpinder; Batra, Aanchal; Singh, Kamal Nain; Mritunjay, Mritunjay (Synthesis, 2021)
1-Aryl-1,2,3,4-tetrahydroisoquinolines are important structural motifs and are widely found in bioactive molecules, pharmaceuticals and synthetic drugs. In view of increasing environmental awareness, the development of transition-metal-free strategies for the synthesis of these compounds is highly desirable. Metal-free oxidative coupling and lithiation methodologies have emerged as effective tools in this area as they exclude the use of transition-metal catalysts and help in reducing unwanted and toxic-metal-based chemical waste in the environment. This review highlights recent advances on the direct arylation of tetrahydroisoquinolines for the synthesis of the title compounds in the absence of a metal salt. Also, the emphasis has been placed on mechanistic considerations of these reactions.1 Introduction2 Arylation of Tetrahydroisoquinolines via Oxidative Coupling2.1 Arylation Using Grignard Reagents2.2 Arylation Using Other Organometallic Reagents2.3 Arylation Using Aryl Organoboranes or Arenes3 Arylation of Tetrahydroisoquinolines via Lithiation3.1 Intermolecular Arylation3.2 Intramolecular Arylation4 Conclusion and Outlook
Keywords: arylation; tetrahydroisoquinolines; oxidative coupling; lithiation; C–H activation; coupling reactions